TEKNOLOGI DAN HIDUP KUDUS: Bagaimana Generasi Z Mengintegrasikan Nilai-Nilai Kristen Dalam Era Digital - Risdayana Rudding; Melda, Femi Yanti Ramme, Delly Itania Ruben, Sriweni Antika Masarrang (CV. ADIBA ASIHA AMIRA, 2025)
This research investigates the complexity of the relationship between digital technology and the understanding and application of Christian values in the lives of Generation Z. As a generation growing up in the digital era, Generation Z faces unique challenges in integrating religious values with the increasingly pervasive use of technology in their daily lives. The study explores the impact of technology on how Generation Z interacts with Christian values, as well as the eflorts and strategies they employ to live a holy life in the digital realm. The research methodology includes surveys and online content analysis to comprehend the behavioral patterns, attitudes, and experiences of Generation Z in integrating Christian values in the digital era. The findings indicate that despite facing temptations from online content conflicting with Christian teachings, Generation Z also utilizes technology to deepen their spiritual beliefs. Churches and religious communities play a central role in providing support, ethical guidance in the digital realm, and community spaces to help Generation Z navigate moral dilemmas in the digital world. The implications of the research underscore the need for a holistic approach from churches and religious communities to support Generation Z in living a holy life amidst the rapid development of technology